The effects of climate change on migratory and resident Arctic whales, and the role of international law towards their conservation - Tiili, Kristin, 1974- (2018)
The thesis set out to find whether climate change affects migratory and resident Arctic whales differently, and the role of international law for their conservation in these uncertain times. The method is desktop research, and information was simply gathered and analysed. The thesis found that the resident Arctic whales are more severely affected by the changes since they are highly ice dependent. The declining sea ice is the main challenge with all its repercussions, such as increasing human traffic in the Arctic for longer periods of time as the sea ice keeps decreasing. International law does not at present have a vast amount of legislation to offer towards the protection of the marine environment and the whales as the treaties presented in this thesis generally directs the obligations to the national legislation of the states. The regional level is somewhat more beneficial towards the protection of the ecosystem, but also the regional agreements leave most of the decisions up to the individual states. The reason for this might partly be because on the regional level more research are carried out that is directed towards the conservation of the marine environment and the whales. In order to improve the current situation, the creation of more MPAs in the Arctic could be a good, or even the best, solution and use of international law moving forward. There are several avenues, and in this thesis OSPAR and the AC are highlighted.